Vibrio cholerae O1 with Reduced Susceptibility to Ciprofloxacin and Azithromycin Isolated from a Rural Coastal Area of Bangladesh - Rashed, Shah M.; Hasan, Nur A.; Alam, Munirul; Sadique, Abdus; Sultana, Marzia; Hoq, Md. Mozammel; Sack, R. Bradley; Colwell, Rita R.; Huq, Anwar (Frontiers in Microbiology, 2017)
Cholera outbreaks occur each year in the remote coastal areas of Bangladesh and epidemiological surveillance and routine monitoring of cholera in these areas is challenging. In this study, a total of 97 Vibrio cholerae O1 isolates from Mathbaria, Bangladesh, collected during 2010 and 2014 were analyzed for phenotypic and genotypic traits, including antimicrobial susceptibility. Of the 97 isolates, 95 possessed CTX-phage mediated genes, ctxA, ace, and zot, and two lacked the cholera toxin gene, ctxA. Also both CTX+ and CTX−V. cholerae O1 isolated in this study carried rtxC, tcpAET, and hlyA. The classical cholera toxin gene, ctxB1, was detected in 87 isolates, while eight had ctxB7. Of 95 CTX+V. cholerae O1, 90 contained rstRET and 5 had rstRCL. All isolates, except two, contained SXT related integrase intSXT. Resistance to penicillin, streptomycin, nalidixic acid, sulfamethoxazole-trimethoprim, erythromycin, and tetracycline varied between the years of study period. Most importantly, 93% of the V. cholerae O1 were multidrug resistant. Six different resistance profiles were observed, with resistance to streptomycin, nalidixic acid, tetracycline, and sulfamethoxazole-trimethoprim predominant every year. Ciprofloxacin and azithromycin MIC were 0.003–0.75 and 0.19–2.00 μg/ml, respectively, indicating reduced susceptibility to these antibiotics. Sixteen of the V. cholerae O1 isolates showed higher MIC for azithromycin (≥0.5 μg/ml) and were further examined for 10 macrolide resistance genes, erm(A), erm(B), erm(C), ere(A), ere(B), mph(A), mph(B), mph(D), mef(A), and msr(A) with none testing positive for the macrolide resistance genes.